The Influence of pelvic-belt design on backpack stability in mountain-biking - Höschler, L.; Frisch, M.; Michel, F. I. (Journal of Science and Cycling, 2021)
The pelvic belt is a common feature amongst modern bike backpacks and is attributed to provide backpack stability. In order to develop functional belts, backpack manufacturers must understand the effects of belt properties on stability and comfort. The goals of this study were to compare the effect of different pelvic belt designs on backpack stability in mountain biking, to test the potential of innovative roll-up belts and to derive findings for further backpack development. The backpack stability of 5 different belt conditions (conventional belt, elastic band, seat-belt and 2 spring balancer conditions) was tested with 11 male recreational cyclists, biking over an uneven ramp. Acceleration data from 4 IMUs placed on the rider (C7, SACRUM) and inside the backpack (TOP, BOTTOM) were used to calculate the respective backpack wobbling (BPW) of the lower and upper region. Subjective feedback was provided with a standardized questionnaire. The only significant differences between the belts were found for the BPW at the bottom region. The conventional belt had significantly smaller BPW values than all other belts. Comparing the roll-up belts, the seat-belt showed significantly lower BPW than the spring balancer. However, a low overall comfort caused by continuous abdominal compression was reported. No differences were found between the two spring forces, highlighting the importance of both belt tension and friction for backpack stability. If further improved roll-up belts could be an innovative feature for bike backpacks.